L’enceinte urbaine d’Aurillac (Cantal) : état des connaissances sur ses origines et son évolution - Marie Caillet (Revue Archéologique du Centre de la France)
In 2019, a preventive archeological excavation in the Frères Charmes block, on a south-east portion of the urban enclosure of Aurillac, made it possible to study the curtain wall elevations, and to gather information on the area through a sedimentary survey. The study of iconography and recent archeological sources, as well as historiography make it now possible to detail the topographic and chronological development of the urban fortifications of Aurillac, and provide material and contextual information concerning their edification.The first fortification associating a masonry curtain wall and defensive ditch would have been a large enclosure built in the first quarter of the 13th century. This structure initially would have protected buildings along communication routes located to the south-west of the primitive town centered around the Saint-Géraud abbey, founded at the end of the ninth century. It is only in the second half of the 14th century, i.e. during the Hundred Years War, that the curtain wall was built around the primitive town to join the first fortification, in particular along the Jordanne River which borders the old town center to the east and contributed to its defence.